2021
DOI: 10.3390/su132413807
|View full text |Cite
|
Sign up to set email alerts
|

Soft Skills Integration into Business Processes Based on the Requirements of Employers—Approach for Sustainable Education

Abstract: This paper deals with the issue of increasing the quality and sustainability of education at universities regarding the requirements of employers. Employers’ expectations of university graduates in terms of soft skills are analysed and outlined. The employers participating in this study answered a questionnaire survey focused on understanding university graduates’ soft skills. The collected results were subjected to the method of mathematical–statistical analysis by nonparametric testing of significance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 11 publications
(14 reference statements)
2
17
0
4
Order By: Relevance
“…The set of soft skills . As we mentioned early, the WEF suggested a set of skills needed for the fourth industrial revolution [ 1 , 50 ], as it is shown in Table 1 . We adapted such proposal to the software development context considering intra and interpersonal attributes.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The set of soft skills . As we mentioned early, the WEF suggested a set of skills needed for the fourth industrial revolution [ 1 , 50 ], as it is shown in Table 1 . We adapted such proposal to the software development context considering intra and interpersonal attributes.…”
Section: Methodsmentioning
confidence: 99%
“…Employers know that professional and technical skills alone cannot help to achieve organizational goals and maintain company competitiveness. The qualities preferred for software developers include technical knowledge within the field or the position as well as soft skills [ 50 ]. Currently, employers consider that to achieve the company’s goals, the employees must master the technical and professional knowledge and superstructure of soft skills.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations